2017
DOI: 10.1111/bjh.14658
|View full text |Cite
|
Sign up to set email alerts
|

SERPINC1 gene mutations in antithrombin deficiency

Abstract: Existing evidence suggests that in most cases antithrombin deficiency can be explained by mutations in its gene, SERPINC1. We investigated the molecular background of antithrombin deficiency in a single centre family cohort study. We included a total of 21 families comprising 15 original probands and sixty-six relatives, 6 of who were surrogate probands for the genetic analysis. Antithrombin activity and antigen levels were measured. The heparin-antithrombin binding ratio assay was used to distinguish between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…We have summarized a practical approach for the diagnostic workup of hereditary AT deficiency in Figure 1. In our experience and according to data from the literature, AT levels of patients with AT deficiency are usually clearly below the normal range (ie, ,80%; most have levels ,70%) 17,41 ; however, patients with type 1 defects can also have levels up to 72% or even 78%. 17,42 AT activity ,70% is highly suggestive of AT deficiency, and a single measurement is sufficient to guide further treatment of VTE patients in the acute phase, particularly if the family history is positive.…”
Section: Comments On Casementioning
confidence: 60%
“…We have summarized a practical approach for the diagnostic workup of hereditary AT deficiency in Figure 1. In our experience and according to data from the literature, AT levels of patients with AT deficiency are usually clearly below the normal range (ie, ,80%; most have levels ,70%) 17,41 ; however, patients with type 1 defects can also have levels up to 72% or even 78%. 17,42 AT activity ,70% is highly suggestive of AT deficiency, and a single measurement is sufficient to guide further treatment of VTE patients in the acute phase, particularly if the family history is positive.…”
Section: Comments On Casementioning
confidence: 60%
“…Previous studies in an Asian population reported that the incidence of antithrombin deficiency in VTE was around 5.9%–9.61% (Liu et al, 1994; Zheng et al, 2009). Most VTE subjects with antithrombin deficiency have been found to carry genetic variants of SERPINC1 (Zeng et al, 2015; Mulder et al, 2017). However, the functional mechanism of variant rs2227589 underlying the levels of antithrombin in plasma remains largely unknown (Anton et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Existing evidence suggests that in most cases antithrombin deficiency can be explained by mutations in its gene SERPINC1 3 . To date, about 300 SERPINC1 gene mutations have been reported to be associated with antithrombin deficiency 4 .…”
Section: Figurementioning
confidence: 99%
“…In 2019, our Thrombosis & Haemostasis Center was contacted by a family member with the question whether we could help elucidate the antithrombin deficiency that runs in the family. As we have a special interest in antithrombin deficiency, 3 we agreed to do so. Because our medical center is located in the Netherlands and participants live in United States of America, we choose to collect saliva instead of blood samples.…”
Section: Figurementioning
confidence: 99%